(untitled) - Hertsgaard, Mark (New York, 1983)
This book introduction energy the struggle for tomorrow, the birth of the atomic brotherhood, the corporate nuclear war, the fall from glory, a sideline business...
Keywords: Nuclear industry,Công nghiệp hạt nhân; United States,Hoa Kỳ